Breast Mass and Lytic Bone Lesions: A Rare Presentation of Non-Hodgkin's Lymphoma Arising in the Breast. (21st October 2013) - Ali, Hira; Yeku, Oladapo; Giesler, Daniel; Campbell-Massa, Ryan; Gao, Faye; Amjad, Ali Imran
Abstract : Background . Primary breast lymphoma is a rare malignancy representing less than 1% of all tumors presenting in the breast. Case Presentation . A 55-year-old woman presented with altered mental status due to severe hypercalcemia and was found to have a large breast mass with lytic bone lesions in the calvarium of the skull. Biopsy of the mass revealed diffuse large B-cell lymphoma. Staging workup did not reveal any visceral organ or distant lymph node involvement. The patient's bone marrow biopsy was positive for involvement with lymphoma. Interestingly, the patient also had a non quantifiable IgA kappa monoclonal protein in the serum. Conclusion . Here, we describe a common presentation in medical oncology, that is, a patient presenting as a clinically advanced breast tumor with hypercalcemia from lytic bone lesions. However, diagnostic workup led to the diagnosis of another common malignancy in an uncommon location, namely, diffuse large B-cell lymphoma arising in the breast.